Systematic identification of regulatory elements in Leukemia. - Komal Tara; Nisar Ahmed Shar; Amna Amin Sethi (International Journal of Endorsing Health Science Research, 2023)
Background: Leukemia is a type of cancer that originates from the bone marrow's blood-forming stem cells. Cancer cells don't follow the usual cellular differentiation and function pathway, so they supersede the healthy cells. Depending on the population and maturity level of abnormal cells, leukemia can be classified as Acute or Chronic. Methodology: We mapped defined leukemia mutations from the COSMIC- The Catalogue of Somatic Mutations to perspective regulatory elements. GeneCards - Human Genes Database and Factorbook were utilized in this work to extract data to analyze gene-centric data related to AML and CML. The chromosomal location, Ensembl version, GRCh37 coordinates, and detailed examination of exons, introns, promoter binding regions, and enhancers were used to investigate co-expressed and differentially expressed genes. Downloaded from Factorbook, the expression levels of healthy and sick genes were compared to known transcription factor binding patterns. Results: When translational control genes become mutated, they begin performing their function excessively, leading to uncontrolled cell proliferation and an accumulation of immature cells in the blood that are unable to perform any function on the one hand and interfering with healthy cells' ability to function optimally due to overpopulation and growth on the other. There is a group of genes whose expression level declines as they are affected by the gene, suggesting that these genes should function as insulators or silencers under normal circumstances. The data for Myc and Max genes were extracted from the Human Genome database and sorted using different techniques to find the common regulatory regions (CRRs). These CRRs were then divided into distinct categories based on the degree to which they co-expressed or their level of expression. Conclusion: Regulatory elements have been identified depending on the values of their expression level and how they are changing concerning the control group. This work will help in understanding the guidelines of blood malignancy at the cellular level by recognizing administrative destinations and are, in this manner, possible focuses for the treatment plans and precession accuracy medication.